Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1994
DOI: 10.1115/94-gt-403
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Timeresolved Radiation Measurements in a Model Gas Turbine Combustor

Abstract: In the context of an extensive experimental investigation of the turbulent, reacting flow in a model gas turbine combustor, the radiation emitted by the confined three-dimensional turbulent propane/air diffusion-flame has been studied. The present study comprises for the first time spectral and time-resolved measurements of the radiative intensity at different axial locations including the reaction zone, the mixing zone and the exit of the model combustor. The radiation measurements are presented together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The contribution due to CO can be neglected due to very low concentration levels. Radiation emitted by CO2 and H20 is confined to defined spectral regions, the radiation bands [ 4] Hence, for an accurate prediction of radiant heat load, this pronounced spectral dependence has been taken into account by application of a Narrow Band Model which is described for example by Brewster To simplify the calculations, the combustion chamber is represented by a cube. The length of the edges have been selected in order to represent the mean lengths of the combustor.…”
Section: Radiation Reflected Radiation W W Wall Emissionmentioning
confidence: 99%
“…The contribution due to CO can be neglected due to very low concentration levels. Radiation emitted by CO2 and H20 is confined to defined spectral regions, the radiation bands [ 4] Hence, for an accurate prediction of radiant heat load, this pronounced spectral dependence has been taken into account by application of a Narrow Band Model which is described for example by Brewster To simplify the calculations, the combustion chamber is represented by a cube. The length of the edges have been selected in order to represent the mean lengths of the combustor.…”
Section: Radiation Reflected Radiation W W Wall Emissionmentioning
confidence: 99%
“…Due to complexity of modelling radiative heat transfer, current radiation calculation practice takes into account only the mean temperature and species fields and ignores their turbulent fluctuations. Spectral and time-resolved measurements in a model gas turbine combustor by Koch et al (1994) have shown highly fluctuating intensities resulting from fluctuations in both temperature and the concentrations of radiating species; it is therefore important to include these fluctuations in radiation calculations. A small number of studies have attempted to develop modelling techniques to include turbulence effects in radiation calculations; these include the work by Song and Viskanta (1986), Kounalakis et al (1981) and Chan et al (1994).…”
Section: Modelling Of Turbulence/radiation Interactions In Combustionmentioning
confidence: 99%